(untitled) (Bangladesh Medical Journal, 2019)
Diabetic retinopathy (DR) is one of the most common causes of blindness in developed countries. Early detection of diabetic retinopathy (DR) is crucial for preventing irreversible blindness. To measure the association of diabetic retinopathy with dabetic foot a cross-sectional study was carried out at Department of Ophthalmology and Surgery, BIRDEM General Hospital, Dhaka from January 2017 to September 2017. Patients were included, who were known diabetic. New cases of type-2 diabetes were also included because they might have complications at the time of diagnosis because of the nature of disease. Mean duration of diabetes was significantly higher in DFU with DR group. BUN and diabetes retinopathy were statistically significant (p<0.05) between two groups. Mean HbA1c, pre-prandial glucose, C-peptide, cholesterol, triglyceride, HDL, LDL, hematocrit, creatinine, ABI, TBI and DM foot ulcer were not statistically significant (p>0.05) between two groups. Most patients (33.3%) had a grade I ulcer in DF with DR group and 33.3% in DF without DR group. Medication taking was significantly high patients who were DF without DR. Combined agents was 11(36.7%) and 11(36.7%) in DF with DR and DF without DR group respectively. Insulin was taken 16(53.3%) in DF with DR group and 19(63.3%) in DF without DR group. Maximum patients had a grade I ulcer in diabetes foot ulcer. Medication taking was significantly high patients who were diabetes foot ulcer than without diabetes foot ulcer. Mean insulin, BUN and diabetes retinopathy was found significantly higher in diabetes with diabetes foot ulcer. Mean insulin BUN and diabetic retinopathy was was significantly higher in diabetes with diabetes foot ulcer. Bangladesh Med J. 2017 Sep; 46 (3): 90-93